Avaliação do reparo ósseo na interface osso/implante em ratas com osteoporose induzida tratadas com raloxifeno ou alendronato: análise histométrica, imunoistoquímica, por epifluorescência e biomecânica - Ferreira, Gabriel Ramalho [UNESP] (2014)
The aim of this study was to evaluate the bone healing in bone/implant interface in rats with induced osteoporosis. The rats underwent bilateral ovariectomy were fed a diet low in calcium. Two groups received drug treatment (raloxifene [OVX RAL] or alendronate [OVX ALE]) and the other group received no medication (OVX NT). The control group underwent sham surgery and was fed a normal diet (SHAM ND). Each animal received an implant on the tibia. The animals were euthanized after 14 or 42 days. The biomechanical analysis (reverse torque), linear extension contact bone / implant (BIC) and bone dynamics periimplantar by the proportion of fluorochrome calcein/alizarin, applying the ANOVA and Tukey's post-test (p<0.05). Immunohistochemistry marked precipitation of osteoprotegerin (OPG), RANKL, TRAP and osteocalcin (OC). The RAL improved drug peri-implant bone repair, wherein the ALE OVX group was similar to the ST group. There were no statistically significant differences in reverse torque (p = 0.861), precipitation of fluorochromes (calcein/alizarin) and BIC between OVX RAL and control groups - SHAM ND (p> 0.05). The immunostaining of OPG and RANKL were similar to RAL and SHAM groups; there was moderate OC expression at 14 days. TRAP was marked intensely at 42 days for the OVX group. Therefore, raloxifene improved peri-implant bone repair of osteoporotic rats, suggesting its indication in the treatment of osteoporosis.